Understanding of Nature of Science Pre-Service Students and Elementary School Teachers in the Digital Age - Ai Hayati Rahayu; Ari Widodo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Understanding the Nature of science (NOS) is very important in the process of learning science in the digital era. Understanding the nature of good science is expected to minimize conceptual errors. This study aims to identify pre-service student responses and elementary school teachers related to understanding the nature of science in the digital age. The type of research conducted is quantitative descriptive with survey method. The study sample consisted of students and elementary school teachers in Sumedang. The instrument used was a questionnaire with 28 statements using a Likert scale. The results of the study stated that the response of students and teachers to the understanding of science in the digital era was in the good category with a percentage of 68.7%. Further analysis using one way ANOVA turned out to have a significant difference between students' understanding of level 3 and 5. The understanding of male and female NOS was not significantly different. While teachers who have been certified have a better average understanding than teachers who have not been certified